Aplikasi MOOC Untuk Pembelajaran Dalam Kualitas MAVIB - Po Abas Sunarya; Henderi Henderi; Wahyu Hidayat (UNIVERSITAS RAHARJA, 2020)
The publication of learning using MOOC in Raharja University is a facility for students and lecturers in learning, learning using MOOC is one of the objectives in the University of Raharja, which will help lecturers in explaining the material so that students are easy to access where I am in the study, the problem is the absence of web learning online using MOOC application, and the absence of information summary to take a decision and the difficulty of the students get information about course or view the material. To solve the problem is conducted research that builds an improvement system of student learning on the quality and quality of university Raharja using SWOT analysis and SPSS (Statistical Product and Service Solutions) method that is felt can help in the management of data. Then transformed in Web Form at Raharja University, it is expected to overcome existing constraints, by providing information that supports the decision-making system in the online learning publications. The system was created with collaborations from Rinfo, Rinfo Sheet, RinfoForm and iLearning Media that are part of the 10 pillars of Raharja University IT. That is further implemented for the needs of student publications at Raharja University through the Web I-Mavib.